Independent work in the educational process of higher engineering and teacher training institutions: current status and perspectives (Pedagogy of Higher and Secondary Education, 2012)
Finohyeyeva T. E. Independent work in the educational process of higher engineering and teacher training institutions: current status and perspectives.In this article оn the basis of studies of modern pedagogical work carried out an analysis of the system of independent work of future teacher- engineers, its teaching conditions and prerequisites. The author offers ways to improve students’ independent work of engineering and teacher training institutions.
Keywords: independent work; self-reliance; teacher-engineer; teaching conditions; teaching prerequisites